Speciality and Fidelity in Translating English Poetry into Arabic»The Hollow Men« (مجلة إحالات, 2026)
Translation is converting a written text from the source language into another one in the targetlanguage, whether we deal with scientific or literary texts. If we want to talk about literary translation,especially poetry, on one hand, we can perceive that the last is the most difficult type of translationat all. On the other hand, some others said that it is impossible to effect such task successfully. Fromwhat it is mentioned above, : This research is focused on translating english poetry into arabic wheresuch process is based on two main factors: speciality and fidelity. The study is aming to determinehow can the former factors impact on selecting methods and techniques adopted by both translatorsto produce an equivalent poetry to the original one as much as possible.